2023
DOI: 10.3390/magnetochemistry9040106
|View full text |Cite
|
Sign up to set email alerts
|

Nylon-6-Coated Doxorubicin-Loaded Magnetic Nanoparticles and Nanocapsules for Cancer Treatment

Abstract: Nanoplatforms used for the loading of anticancer drugs constitute a promising approach to cancer treatment and reducing the side effects of these drugs. Among the cutting-edge systems used in this area are magnetic nanocomposites (MNCs) and nanocapsules (NCs). MNCs are considered to constitute a smart tool for magnetic-field-guided targeted drug delivery, magnetic resonance imaging, and hyperthermia therapy. Nanocapsules offer great potential due to their ability to control drug-loading capacity, their release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 105 publications
0
5
0
Order By: Relevance
“…The dynamic light-scattering (DLS), zeta-potential and polydispersity index measurements were taken on a Malvern Zetasizer Nano device (Malvern Instruments, Worcestershire, UK) at 37 °C in solutions with different ratios of viral particles (2. 8 × 10 8 PFU/mL) to aptamer (10 μM) and different dilutions in serum [ 44 ]. All DLS results were calculated as the average of at least triplicate measurements and presented as mean ± SD.…”
Section: Methodsmentioning
confidence: 99%
“…The dynamic light-scattering (DLS), zeta-potential and polydispersity index measurements were taken on a Malvern Zetasizer Nano device (Malvern Instruments, Worcestershire, UK) at 37 °C in solutions with different ratios of viral particles (2. 8 × 10 8 PFU/mL) to aptamer (10 μM) and different dilutions in serum [ 44 ]. All DLS results were calculated as the average of at least triplicate measurements and presented as mean ± SD.…”
Section: Methodsmentioning
confidence: 99%
“…The magnetic composites demonstrated good loading capacity and pH-dependent release behavior. Cytotoxicity studies were performed on lung cancer cell lines and showed increased toxicity of the DDS compared to free DOX [ 153 ].…”
Section: Chemotherapy Delivery Using Magnetic Nanoparticlesmentioning
confidence: 99%
“…MNIP and MMIP had almost the same FTIR spectrum due to the same nylon-6 and MNP nature (Figure 7). The characteristic peaks were found at 1260 (C-N, N-H), 1382 (CH 2 wagging), 1550 (C-N, N-H), 1652 (amide C=O stretch), 2869 (CH 2 symmetric stretch), 2936 (CH 2 asymmetric stretch), 3307 (N-H stretch), and 3440 cm −1 (O-H and N-H stretch) [43,[57][58][59], which shows a good correlation with nylon-6 polymer (see https://spectra.chem.ut.ee/textile-fibres/polyamide/, accessed on 28 June 2023). Moreover, broad peaks at 580-700 cm −1 corresponded to a combination of nylon and magnetite stretches.…”
Section: Synthesis Of Magnetic Imprinted Polymers (Mmips) and Magneti...mentioning
confidence: 99%
“…Nowadays, coated MNPs find vast applications in nanomedicine, magnetic separation, imaging, and theranostics [28,29,[45][46][47][48][49]. Previously [39,43], we have shown the possibility of nylon coating on MNPs for nucleic acid microextraction and therapeutic applications. The proposed approach makes it possible to design polymer matrices for various tasks; for example, sensing surfaces or microparticle sorbents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation